2022
DOI: 10.1002/ejp.2055
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of neuropathic pain associated with coronavirus disease 2019

Abstract: Background and Objective Neuropathic pain is an occasionally reported complication of coronavirus disease 2019 (COVID‐19) that has received increased attention in scientific literature. In this systematic review and meta‐analysis, we aimed to provide information on the frequency of neuropathic pain associated with COVID‐19. Databases and Data Treatment We systematically reviewed and analysed literature regarding neuropathic pain associated with COVID‐19. Literature searches were conducted in PubMed, EMBASE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Contrastingly, very few data are available for neuropathic pain. A recently published metanalysis has estimated it to occur in 10% (95% CI 5%–15%) of patients during acute/subacute COVID‐19 (di Stefano et al, 2023), but few studies have assessed its frequency and characteristics in the long run. Chronic neuropathic pain has been reported to occur in 24.6% of new‐COVID‐P patients (Herrero‐Montes et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, very few data are available for neuropathic pain. A recently published metanalysis has estimated it to occur in 10% (95% CI 5%–15%) of patients during acute/subacute COVID‐19 (di Stefano et al, 2023), but few studies have assessed its frequency and characteristics in the long run. Chronic neuropathic pain has been reported to occur in 24.6% of new‐COVID‐P patients (Herrero‐Montes et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While studies have been conducted to investigate neuropathic pain during the acute phase of COVID-19 infection, the frequency and characteristics of this pain in the long term have only been investigated in a limited number of studies [25,26]. A study showed that 24.6% of new COVID-19 patients report chronic neuropathic pain after 6 months of infection [27].…”
Section: Neuropathic Pain Symptommentioning
confidence: 99%
“…A recent meta-analysis estimated that the frequency of post-COVID neuropathic pain ranged between 0.4 and 25% [ 81 ] . Another study reported the prevalence of “de novo” post-COVID neuropathic pain in almost 25% of previously hospitalized COVID-19 survivors.…”
Section: Prevalence Of Post-covid-19 Painmentioning
confidence: 99%